RESTITUSI TINDAK PIDANA PEMBUNUHAN DI WILAYAH KEJAKSAAN NEGERI BUNGO - Adhi Wibowo (Ekasakti Jurnal Penelitian dan Pengabdian, 2023)
Victims, families or heirs can apply for compensation, which is called restitution. The victim, family or heirs first submit a request for restitution to the Witness and Victim Protection Agency, then the Witness and Victim Protection Agency issues a decision letter for restitution to the Police, the Public Prosecutor and the Panel of Judges. The type of research used is the empirical method. Restitution in the Public Prosecutor's Charges Against Victims of the Crime of Murder in the Legal Area of the Bungo State Prosecutor's Office in Case Number 249/Pid. B/ PN Mrb, the Public Prosecutor received a decision letter for restitution from the Witness and Victim Protection Agency. Then the Public Prosecutor combined the decision letter for restitution into the lawsuit, with the nominal loss suffered by the victim, namely Rp. 145,000,000 (one hundred and forty-five million rupiah). The Public Prosecutor incorporates restitution into the demand letter by considering certainty, benefit and fairness.